Studi Kasus Susah Tidur Pada Kehamilan Trimester III dengan Terapi Senam Hamil Case Study of Struggling to Sleep in Trimester III Pregnancy with Pregnant Gymnastics Therapy - Dessy Hidayati Fajrin; Lidia (Ovary Midwifery Journal, 2023)
Some of the inconveniences experienced by pregnant women include nausea and vomiting, easy fatigue, frequent urination, or difficulty resting and others. One of the conditions experienced by pregnant women in the third trimester is insomnia. What causes sleep disturbances in pregnant women are physical and emotional changes during pregnancy. Physical changes that occur such as nausea and vomiting in the morning, increased frequency of urination, uterine enlargement, back pain and fetal movement. Emotional changes include anxiety, fear and depression. According to the National Sleep Foundation Survey (2018), 97.3% of third trimester pregnant women always wake up at night. An average of 3-11 times every night, and 78% of pregnant women in America experience sleep disorders. The role of midwives in helping mothers reduce complaints of difficulty sleeping is by suggesting exercise. The most suitable type of exercise for pregnant women is pregnant gymnastics. The research conducted used descriptive qualitative with a case study approach, and field observations. Midwifery care assessment in clients with pregnancy is carried out basic data collection, namely subjective data and objective data. After the intervention of doing pregnant gymnastics, the patient's subjective data includes: Mrs.H age 32 years G3P2A0M0 pregnant 35 weeks, can already sleep 7-8 hours a day comfortably. Based on the results of the examination, objective data obtained the patient's general condition is good, composmentis consciousness, vital signs: blood pressure 97/79 mmHg, pulse 82 times/minute, breathing 22 times/minute, temperature 36.7°C. No abnormalities were found on physical examination or on supporting examinations, complaints of difficulty in sleeping have been resolved.